Factors For Increasing Export of Tourism Services (Zien Journal of Social Sciences and Humanities, 2023)
This article points out the importance of tourism to the economy of Uzbekistan and ways of increasing export of tourism services. Moreover, a number of major factors that will lead tourism factors to steady development are also identified in the article